Mild and Asymptomatic COVID-19 Convalescents Present Long-Term Endotype of Immunosuppression Associated With Neutrophil Subsets Possessing Regulatory Functions - Siemińska, Izabela; Węglarczyk, Kazimierz; Surmiak, Marcin; Kurowska-Baran, Dorota; Sanak, Marek; Siedlar, Maciej; Baran, Jarek (Frontiers in Immunology, 2021)
The SARS-CoV-2 infection (coronavirus disease 2019 - COVID-19) is associated with severe lymphopenia and impaired immune response, including expansion of myeloid cells with regulatory functions, e.g. so called low density neutrophils, containing granulocytic myeloid-derived suppressor cells (LDNs/PMN-MDSCs). These cells have been described both in infections and cancer and are known for their immunosuppressive activity. In the case of COVID-19, long-term complications have been frequently observed (long-COVID). In this context we aimed to investigate the immune response of COVID-19 convalescents after a mild or asymptomatic course of disease. We enrolled 13 convalescents who underwent a mild or asymptomatic infection with SARS-CoV-2, confirmed by a positive result of the PCR test, and 13 healthy donors without SARS-CoV-2 infection in the past. Whole blood was used for T cell subpopulation and LDNs/PMN-MDSCs analysis. LDNs/PMN-MDSCs and normal density neutrophils (NDNs) were sorted out by FACS and used for T cell proliferation assay with autologous T cells activated with anti-CD3 mAb. Serum samples were used for the detection of anti-SARS-CoV-2 neutralizing IgG and GM-CSF concentration. Our results showed that in convalescents, even 3 months after infection, an elevated level of LDNs/PMN-MDSCs is still maintained in the blood, which correlates negatively with the level of CD8+ and double-negative T cells. Moreover, LDNs/PMN-MDSCs and NDNs showed a tendency for affecting the production of anti-SARS-CoV-2 S1 neutralizing antibodies. Surprisingly, our data showed that in addition to LDNs/PMN-MDSCs also NDNs from convalescents inhibit proliferation of autologous T cells. Additionally, in the convalescents sera we detected significantly higher concentrations of GM-CSF, indicating the role of emergency granulopoiesis. We conclude, that in mild or asymptomatic COVID-19 convalescents the neutrophil dysfunction, including propagation of PD-L1 positive LDNs/PMN-MDSCs and NDNs is responsible for long-term endotype of immunosuppression.